Bilayer 3D co‐culture platform inducing the differentiation of normal fibroblasts into cancer‐associated fibroblast like cells: New in vitro source to obtain cancer‐associated fibroblasts - Yeon Ju Kim; Hyeon Song Lee; Dohyun Kim; Hwa Kyung Byun; Woong Sub Koom; Won‐Gun Koh (Bioengineering & Translational Medicine)
Abstract This study presents a novel in vitro bilayer 3D co‐culture platform designed to obtain cancer‐associated fibroblasts (CAFs)‐like cells. The platform consists of a bilayer hydrogel structure with a collagen/polyethylene glycol (PEG) hydrogel for fibroblasts as the upper layer and an alginate hydrogel for tumor cells as the lower layer. The platform enabled paracrine interactions between fibroblasts and cancer cells, which allowed for selective retrieval of activated fibroblasts through collagenase treatment for further study. Fibroblasts remained viable throughout the culture periods and showed enhanced proliferation when co‐cultured with cancer cells. Morphological changes in the co‐cultured fibroblasts resembling CAFs were observed, especially in the 3D microenvironment. The mRNA expression levels of CAF‐related markers were significantly upregulated in 3D, but not in 2D co‐culture. Proteomic analysis identified upregulated proteins associated with CAFs, further confirming the transformation of normal fibroblasts into CAF within the proposed 3D co‐culture platform. Moreover, co‐culture with CAF induced radio‐ and chemoresistance in pancreatic cancer cells (PANC‐1). Survival rate of cancer cells post‐irradiation and gemcitabine resistance increased significantly in the co‐culture setting, highlighting the role of CAFs in promoting cancer cell survival and therapeutic resistance. These findings would contribute to understanding molecular and phenotypic changes associated with CAF activation and provide insights into potential therapeutic strategies targeting the tumor microenvironment.